Critical Remarks on Ernesto Laclau's Populism (Papeles, 2021)
In this article we make several critical remarks on Ernesto Laclau's populism. We start analyzing the first article published by Laclau in New Left Review, on the "Cordobazo", the social uprising which took place in Argentina in 1969. Then we analyze the inconsistencies of the articles included in Laclau's book, Politics and Ideology in Marxist Theory. Finally, we analyze the theoretical and practical limitations of Laclau's masterpiece On Populist Reason.
Keywords: Ernesto Laclau; populism; postmarxism; Argentina; neoliberalism